Outsourcing Memory in Response to an Aging Population. (November 2015) - Ross, Michael; Schryer, Emily
With baby boomers entering old age and longevity increasing, policymakers have focused on the physical, social, and health needs of older persons. We urge policymakers to consider cognitive aging as well, particularly normal, age-related memory decline. Psychological scientists attribute memory decline mainly to cognitive overload stemming from age-related reductions in sensory capacities, speed of cognitive processing, and the ability to filter out irrelevant information. Even in the absence of decline, however, memory is imperfect and forgetting can be especially consequential for older adults. For example, forgetting to take prescription medicines is an age-related problem largely because older adults tend to ingest many more prescription drugs. We propose that policymakers focus on increasing environmental support for memory that can reduce the burden on cognitive resources and thus improve recall. In providing environmental support, policymakers need to pay careful attention to potential age-related changes in physical and cognitive capacity, as well as behavior.